2017
DOI: 10.1111/echo.13750
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left ventricular reverse remodeling in patients with severe aortic regurgitation undergoing aortic valve replacement: Comparison between diameters and volumes

Abstract: Compared to the volume-based method, diameter-based LV measurement incorrectly identified LV reverse remodeling post-AVR in 17% of patients with severe AR. Left ventricle (LV) volume may be a better measure to assess LV remodeling post-AVR than LV diameter-based measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Although it is stated to be safe for adult cardiac surgery, more studies are needed on specific subgroups. Conditions requiring aortic valve replacement (aortic stenosis and aortic regurgitation) should also be subject to a separate assessment in terms of their effects on the left ventricle 3 , 4 . However, there is still a limited number of data associated with the use of DNC in aortic valve replacement 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Although it is stated to be safe for adult cardiac surgery, more studies are needed on specific subgroups. Conditions requiring aortic valve replacement (aortic stenosis and aortic regurgitation) should also be subject to a separate assessment in terms of their effects on the left ventricle 3 , 4 . However, there is still a limited number of data associated with the use of DNC in aortic valve replacement 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…46 In patients with severe aortic regurgitation undergoing treatment with either transcatheter aortic valve implantation 47 or aortic valve surgery, LV volume decreased an average of 30% to 35%. 48,49 Therefore, the cardiac structural improvements seen in our patients post-HSCT are within the clinically significant range.…”
Section: Hgbmentioning
confidence: 65%
“…AR associated with LV volumes overload and pressure overload, preoperative LVEF and left ventricle systolic dimension presented the pump performance, and left ventricle diastolic dimension presented the severity of volumes overload. Although AVR could correct the hemodynamic disturbance in AR patients, previous reports have suggested that the improvement of left ventricle function after aortic valve replacement early phase was due to the reduction of LV volume overloading [ 13 , 14 ]. In this study, the mean LV diastolic dimension and LV ejection fraction were 70.2 mm and 50.5% in remodeling patients, but they were 80.6 mm and 37.7% for the no remodeling patients.…”
Section: Discussionmentioning
confidence: 99%